Hispanismos y canarismos en un corpus de textos ingleses sobre Canarias - González-Cruz, María-Isabel (2013)
Las Islas Canarias (España) siempre han mantenido un estrecho contactocon el mundo anglosajón, lo que ha generado importantes consecuencias económicas, así como también socioculturales, lingüísticas y literarias. Un análisis de la bibliografía inglesa sobre Canarias revela, entre otros aspectos, la tendencia al uso de hispanismos y canarismos. Este trabajo ofrece el registro de esas voces que aparecen en un corpus de catorce obras tomadas de la extensa bibliografía anglocanaria. Tras revisar brevemente la relevancia del hispanismo inglés, nuestra recopilación intenta resaltar la contribución del español de Canarias al enriquecimiento del vocabulario de la lengua inglesa, constatando cuáles de los hispanismos de nuestro corpus que son canarismos han pasado al registro lexicográfico realizado por elShorter Oxford English Dictionary on Historical Principles (2007).AbstractThe Canary Islands (Spain) have always been in close contact with the Anglo-Saxon world, which has had important consequences for the economy but also at the socio-cultural, linguistic and literary levels. A review of the English bibliography on the Canaries reveals, among other aspects, a tendency in most authors to use hispanicisms and canarianisms in their texts. This article offers a record of those words which appear in a corpus of fourteen works taken from this extensive bibliography. Apart from providing an overview of the studies on hispanicisms in English, this paper’s main aim is to highlight the contribution of Canarian Spanish to the enrichment of the vocabulary of English by checking which of the hispanicisms in our corpus, which are actually canarianisms, have been included in the lexical repertoire of the Shorter Oxford English Dictionaryon Historical Principles (2007).